Mobile communication and the protection of children - Ong, Rebecca, 1961-; ebrary, Inc.; E.M. Meijers Instituut (Leiden : Leiden University Press, 2010)
Mobile phones and other smart connected devices have fundamentally changed contemporary life. Globally, we see an unprecedented explosion of new generation mobile phones. More precisely, mobile communication is nowadays really pervasive in social life. For instance, children and young persons are emerging as active players in the wonderful world of ringing and being ringed. Many of them are attracted by intriguing ring tones. However, the rapid mobile diffusion among children and young people raises a number of crucial questions--
On cover: E.M. Meijers Instituut.
"Proefschrift ter verkrijging van de graad van Doctor aan de Universiteit Leiden, op gezag van de Rector Magnificus prof. mr. P.F. van der Heijden, volgens besluit van het College voor Promoties te verdedigen op donderdag 22 april 2010 klokke 11.15 uur.
Thesis (Doctoral)--University of Leiden, 2010.
Includes bibliographical references (p. [319]-345).
Electronic reproduction.
In English with a summary also in Dutch.
Keywords: Cell phone services industry -- Law and legislation; Cell phones -- Social aspects; Cell phone advertising; Cell phones and teenagers; Youth -- Legal status, laws, etc; Children -- Legal status, laws, etc; Electronic books